Pengaruh Budaya Lisan Terhadap Narasi dalam Sastra Melayu Klasik - Mira Anggraini; Putri Ramadani; Tria Putri Andini; Igha Devira Pristine; Dinda Fatimatuz Zahra; Akmal Akmal (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Malay literature is written work originating from Malay culture and traditions. Malay literature has a long history that reflects the culture, religion and social life of Malay society. Literature plays an important role in shaping the character of a country which can create a beautiful impression on those who see it. Malay literature which is based on values ​​not only colors the lives of nobles, but also among ordinary people. Malay culture contains morals that greatly contribute to the formation of Indonesian society. In the study of Malay literature, there are 2 aspects that must be studied and instilled in the nation's future generations, namely classical Malay literary works and modern literary works. So that Malay culture is not lost over time.